Development of a TLR7/8 agonist adjuvant formulation to overcome early life hyporesponsiveness to DTaP vaccination - David J. Dowling; Soumik Barman; Alyson J. Smith; Francesco Borriello; Danielle Chaney; Spencer E. Brightman; Gandolina Melhem; Byron Brook; Manisha Menon; Dheeraj Soni; Simone Schüller; Karthik Siram; et al. (Scientific Reports, 2022)
Abstract Infection is the most common cause of mortality early in life, yet the broad potential of immunization is not fully realized in this vulnerable population. Most vaccines are administered during infancy and childhood, but in some cases the full benefit of vaccination is not realized in-part. New adjuvants are cardinal to further optimize current immunization approaches for early life. However, only a few classes of adjuvants are presently incorporated in vaccines approved for human use. Recent advances in the discovery and delivery of Toll-like receptor (TLR) agonist adjuvants have provided a new toolbox for vaccinologists. Prominent among these candidate adjuvants are synthetic small molecule TLR7/8 agonists. The development of an effective infant Bordetella pertussis vaccine is urgently required because of the resurgence of pertussis in many countries, contemporaneous to the switch from whole cell to acellular vaccines. In this context, TLR7/8 adjuvant based vaccine formulation strategies may be a promising tool to enhance and accelerate early life immunity by acellular B. pertussis vaccines. In the present study, we optimized (a) the formulation delivery system, (b) structure, and (c) immunologic activity of novel small molecule imidazoquinoline TLR7/8 adjuvants towards human infant leukocytes, including dendritic cells. Upon immunization of neonatal mice, this TLR7/8 adjuvant overcame neonatal hyporesponsiveness to acellular pertussis vaccination by driving a T helper (Th)1/Th17 biased T cell- and IgG2c-skewed humoral response to a licensed acellular vaccine (DTaP). This potent immunization strategy may represent a new paradigm for effective immunization against pertussis and other pathogens in early life.